Target-specific delivery of peptide-based probes for PET imaging - Chen, Kai; Conti, Peter S. (Advanced drug delivery reviews, 2010)
Positron emission tomography (PET) is one of the most rapidly growing areas of medical imaging, with many applications in the clinical management of patients with various diseases. The principal goal of PET imaging is to visualize, characterize, and measure biological processes at the cellular, subcellular, and molecular level in living subjects with non-invasive procedures. PET imaging takes advantage of the traditional diagnostic imaging techniques and introduces positron-emitting probes to determine the expression of indicative molecular targets at different stages of disease. During the last decade, advances in molecular biology have revealed an increasing number of potential molecular targets, including peptide receptors and peptide-related biomolecules. With the help of sophisticated bioconjugation and radiolabeling techniques, numerous peptide-based agents have been developed and evaluated for delivery of PET radionuclides to the specific molecular targets in preclinical and clinical studies. As compared to macromolecules, such as proteins or antibodies, low-molecular-weight peptides have their distinctive advantages and predominantly demonstrate their favorable pharmacokinetics for in vivo PET applications. This review summarizes the criteria of peptide-based PET probes design, the selection of radioisotopes, labeling methods, and provides an overview of the current status and trends in the development of target-specific peptide-based probes with respect to their unique PET imaging applications. [Display omitted]